2021
DOI: 10.1007/s00415-021-10677-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of CIDP one year after start of treatment: a prospective cohort study

Abstract: Objective To assess clinical outcome in treatment-naive patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP). Methods We included adult treatment-naive patients participating in the prospective International CIDP Outcome Study (ICOS) that fulfilled the European Federation of Neurological Societies/Peripheral Nerve Society (EFNS/PNS) diagnostic criteria for CIDP. Patients were grouped based on initial treatment with (1) intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…OCBs also indicated to be very appreciable factor, as they were found in only one patient in non-CIDP group vs almost 30% of confirmed CIDP subjects, which follows the finding of a recent study. 27 Of great importance is another supportive criterion -response to therapy, that turned out to be very precise to distinguish between CIDP and non-CIDP groups. Thus, CIDP patients are still often treated by trials and errors.…”
Section: Resultsmentioning
confidence: 99%
“…OCBs also indicated to be very appreciable factor, as they were found in only one patient in non-CIDP group vs almost 30% of confirmed CIDP subjects, which follows the finding of a recent study. 27 Of great importance is another supportive criterion -response to therapy, that turned out to be very precise to distinguish between CIDP and non-CIDP groups. Thus, CIDP patients are still often treated by trials and errors.…”
Section: Resultsmentioning
confidence: 99%
“…However, the heterogeneity of CIDP creates challenges and delays in diagnosis. The ICOS study indicated that the time between disease onset and treatment was 11 months, and delayed-treated patients had a more severe disability ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events associated with citrate use, difficulty with venous access, and hemodynamic changes have been reported in plasma exchange patients. In some cohorts, 60–70% of the CIDP patients reported problems with mobility, self-care, usual activities, pain, or discomfort in IVIg and methylprednisolone ( 9 ). It is inspiring to be here and see how TCM can be used to ensure efficacy and safety in the literature review and case report.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most patients (94%) started with IVIG, neurological symptoms improved. Remission was found in 44% of patients started with combined treatment [ 44 ].…”
Section: Chronic Inflammatory Demyelinating Polyneuropathymentioning
confidence: 99%